Sustained censorship in TH (2026-06) (Thailand) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Thailand. Data sourced from OONI.
Censorship Incident ID: TH-2026-0154. Severity: critical. Confidence: 77%